Application of the advance incision in robotic-assisted laparoscopic rectal anterior resection - Qiu, Yuhao; Li, Ying; Chen, Zhenzhou; Chai, Ninghui; Liang, Xianping; Zhang, Dahong; Wei, Zhengqiang (Frontiers in Surgery, 2023)
Background: The incidence of rectal cancer is increasing each year. Robotic surgery is more frequently being used in the surgical treatment of rectal cancer; however, several problems associated with robotic surgery persist, such as moving robot system repeatedly to make auxiliary incisions and difficulty in exposing the operation field of obese patients. Here, we introduce a new technology that effectively improves the operability and convenience of robotic rectal surgery. Objectives: To simplify the surgical procedure, enhance operability, and improve healing of the surgical incision, we aimed to develop an advance incision (AI) technique for robotic-assisted laparoscopic rectal anterior resection, and compare its safety and feasibility with those of intraoperative incision. Methods: Between January 2016 and October 2021, 102 patients with rectal cancer underwent robotic-assisted laparoscopic rectal anterior resection with advance or intraoperative (iOI) incisions. Perioperative, incisional, and oncologic outcomes were compared between groups. Results:No significant differences in the operating time, blood loss, time to first passage of flatus, time to first passage of stool, duration of hospitalization, and rate of overall postoperative complications were observed between groups. The mean time to make auxiliary incisions was shorter in the AI group than the iOI group (14.14 min vs. 19.77 min; p< 0.05). The average incision length was shorter in the AI group than the iOI group (6.12 cm vs. 7.29 cm; p< 0.05). Postoperative incision pain (visual analogue scale) was lower in the AI group than the iOI group (2.5 vs. 2.9 p=0.048). No significant differences in incision infection, incision hematoma, incision healing time, and long-term incision complications, including incision hernia and intestinal obstruction, were observed between groups. The recurrence (AI group vs. iOI group=4.0% vs. 5.77% ) and metastasis rates (AI group vs. iOI group=6.0% vs. 5.77% ) of cancer were similar between groups. Conclusions: The advance incision is a safe and effective technique for robotic-assisted laparoscopic rectal anterior resection, which simplifies the surgical procedure, enhances operability, and improves healing of the surgical incision.